Ecological Education in Church Documents and Canon Law - Piotr Krajewski (Nicolaus Copernicus University in Toruń, 2011)
The environment determines the existence of man who nowadays is considered to be the main and sometimes the sole protagonist of transformations. Man connects its existence with nature, he depends upon it and at the same time he conditions its existence from its good or ill will. He possesses the tools and knowledge about the possibilities of nature's transformation and even annihilation of it which makes him occupy a unique position in the universe. Therefore, efforts to protect the environment of life must be multidirectional and coordinated. It is possible that in future modern biotechnology will be the solution for sustainable development, which provides the possibility to exercise control over economy and directs scientific research. Making any decision in this area involves the responsibility of international institutions, government, and citizens. Hence, it is important to create a situation in which the development and use of modern technologies, knowledge and skills, are in conditions which ensure maximum safety and exclude needless risk to humans and the environment of their lives.